Growth Increments of Indigenous Species Planted in Secondary Forest Area - Hassan, Affendy; Mohamad, Aminuddin; Wahab, Razak; Mojiol, Andy Russel (2009)
Evaluation on the growth of five indigenous timber species was performed after nine years after planting. The selected species was Azadirachta excelsa, Cinnamomum iners, Hopea pubescens, Intsia palembanica and Shorea leprosula planted under open area planting technique on secondary forest area were carried out in Pasoh Forest Reserve Area, Negeri Sembilan. The assessment involving measurements of Diameter at Breast Height (DBH), height of the species and the survival rate were carried out. An experimental design of Randomized Complete Block Design (RCBD) was adapted. The result shows that the higher growth increments for the DBH were found at A. excelsa (1.06 cm year-1) and the lowest at, I. palembanica (0.97 cm year-1). For the height increment, A. excelsa was 1.38 m year-1 which was the higher and the lowest was the C. iners (0.77 m year-1). However, the survival rate found higher at C. iners (76.3%) and the lowest was at the S. leprosula (20.7%). This indicates that some indigenous species can be adapted to rehabilitate secondary forest area.